PELATIHAN PEMELIHARAAN WEBSITE DI LINGKUNGAN SEKOLAH DI WILAYAH DESA MUARA GEMBONG KECAMATAN MUARA GEMBONG KABUPATEN BEKASI PROPINSI JAWA BARAT - Diat Nurhidayat; Muhammad Ficky Duskarnaen (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract Service to the Community of the Faculty's Featured Foster Areas in 2022 will be held in Muara Gembong Village.Muara Gembong Village is at the far end of Bekasi Regency, bordering the Java Sea to the north, Jakarta Bay tothe west, Karawang Regency to the east, and Babelan sub-district to the south, and has a population of 40,000.Observations show that the schools in the village do not have an active school website and the school does notyet have human resources to manage the school website. A school website contains important information about the actual school and must always be maintained, the information and news must always be updated. Based on the problem, Community Service activities are directed at providing Website Maintenance Training in the School Environment with the aim that the school's website will be active again while at the same time providing expertise to school HR to maintain and manage the school's website. The implementation method begins with internal consolidation, then continues with coordination with partners. The implementation was carried out at the school attended by teachers and the foundation. After the training we provide 1 month online technical guidance. Through the WDLC (Web Development Life Cycle) method, we produce a school website. The presence of this website has an impact on the emergence of the potential for further development of website learning and provides opportunities to learn to build the contents of the website. The school welcomes the presence of the school website. Abstrak Pengabdian kepada Masyarakat Wilayah Binaan Unggulan Fakultas tahun 2022 dilaksanakan di Desa MuaraGembong. Desa Muara Gembong berada paling ujung di Kabupaten Bekasi, berbatasan Laut Jawa di utara,Teluk Jakarta di barat, Kabupaten Karawang di timur, dan kecamatan Babelan di selatan, dan memiliki penduduk 40.000 jiwa. Pada pengamatan terlihat sekolah-sekolah yang ada didesa tersebut, tidak memiliki website sekolah yang aktif dan sekolah belum memiliki SDM untuk mengelola website sekolah. Sebuah website sekolah memuat informasi penting tentang sekolah secara aktual dan harus selalu terpelihara, informasi dan beritanyapun harus selalu update. Berdasarkan permasalahan maka kegiatan Pengabdian kepada Masyarakat diarahkan untuk memberikan Pelatihan Pemeliharaan Website Di Lingkungan Sekolah dengan tujuan agar web sekolah akan aktif kembali sekaligus memberikan keahlian kepada SDM disekolah untuk memelihara dan mengelola web sekolah. Metode pelaksanaan diawali dengan konsolidasi internal, kemudian dilanjutkan koordinasi dengan mitra. Pelaksanaan dilakukan disekolah dihadiri oleh guru dan pihak yayasan. Selesai pelatihan kami memberi bimbingan teknis online 1 bulan. Melalui metode WDLC (Web Development Life Cycle), kami menghasilkan website sekolah. Hadirnya website ini berdampak pada munculnya potensi pengembangan pembelajaran website lebih jauh dan memberi kesempatan untuk belajar membangun isi website tersebut. Pihak sekolah menyambut sangat baik hadirnya web sekolah.